Understanding Islamic charities - Alterman, Jon B.; VonHippel, Karin (Significant issues series / Center for Strategic and International Studies, 2007)
Islamic charities, faith-based organizations, and the international aid system / Jonathan Benthall -- Recognizing the Umma in humanitarianism : international regulation of Islamic charities / James Shaw-Hamilton -- Aid effectiveness : improving relations with Islamic charities / Karin von Hippel -- Islamic charities after catastrophes : the Kashmir earthquake and the Indian Ocean tsunami / John Ratcliffe -- Saudi charities and support for terror / Jon B. Alterman -- Islamic charities in Europe / Julianne Smith and Natalia Filipiak -- Hamas : resistance and the transformation of Palestinian society / Haim Malka -- Hizballah : Islamic charity in Lebanon / A. Nizar Hamzeh -- Islamic charities in Somalia / Andre Le Sage